Development and Implementation of a Smart Parking Spot Allocation System Based on the User’s Category and Priority using Verilog HDL - Rosli, Nuraliah Alwani; Mohamad Hadis, Nor Shahanim; Abdullah, Samihah; Ibrahim, Mohamad Nizam; Abdullah, Mohd Hanapiah; Isa, Iza Sazanita (Journal of Electronic Voltage and Application, 2022)
Finding parking spots for automobiles is a major issue in many large and congested cities. Usually, drivers lose time searching for parking spots, especially during peak hours, which increases traffic congestion and makes drivers frustrated and annoyed. Large building parking areas could also become dangerous to women, pregnant women, and the elderly, as several criminal cases in the parking area, were reported. In this project, a prototype of a smart parking spot allocation system based on the user’s category and priority was developed. The choice of user categories is people with disabilities (OKU), pregnant women/elderly, women, and normal users. The highest priority is assigned to OKU, followed by pregnant women/elderly, followed by women and the lowest priority is assigned to normal users. The parking spots for the highest priority category are placed near building entrances such as mall entrances. The controller for the automatic parking spot allocation system was developed using Verilog HDL code and the prototype was implemented on FPGA DE2-115. The controller is programmed to process the user’s category which is selected by the user at the second entrance and assign a specific parking spot number according to the category’s priority. The prototype was tested with multiple parking spots condition with different user inputs for different user categories. The system was able to allocate parking spots based on the user’s category depending on the parking spot available for the selected category with 75% out of 12 tests correct. However, all 12 tests, or 100% recorded accurate allocation based on the expected output of the system design. In a conclusion, this proposed system would be able to cater to the issue of finding parking spots hence directly avoiding traffic congestion and frustration among users. In addition, this system can indirectly reduce crime cases in the parking area due to parking spaces that prioritize categories of users needing to be parked near the entrance.